(untitled) (Medical Forum Monthly, 2024)
Objective: Diabetes is a heterogeneous disease characterized by relative or absolute insulin deficiency. Reports have shown that trace elements and minerals lead to the pathology of obesity and diabetes due to their participation in per oxidation and inflammation. So the present study is aimed to investigate the relationship between serum copper levels and duration of diabetic condition. Study Design: Observational / descriptive study. Place and Duration of Study: This study was conducted at the Department of Biochemistry, Liaquat College of Medicine and Dentistry and Darul Sehat Hospital, Karachi from __ Materials and Methods: For this purpose we have selected participants (n=120) on the basis of their history were divided accordingly into four groups; control group, diabetic duration 0-5years, diabetic duration 6-10 years, diabetic duration 10 years onwards. After monitoring their demographic parameters the blood sample was collected for the estimation of FBS, HBA1c and copper levels. Results: Results have showed a significant rise in FBS, HBA1c and copper levels in all three diabetic groups compared to control (non-diabetic) individuals. Then correlation analysis has showed that levels of copper have a positive correlation with diabetic parameters indicating that copper levels were increased as the diabetic condition progresses. Conclusion: Hence, blood copper levels are responsible for incidence and progression of diabetes mellitus. As the copper levels in blood are increasing gradually during diabetic condition.